The Effectiveness of School Library Services as a Student Learning Resource in Changing Student Behavior in the History Subject at State Vocational High School 1 Siniu - Nurafifa Nurafifa; Iskandar Iskandar; Nuraedah Nuraedah; Minarni Nongtji (MASI Mandiri Edukasi, 2026)
This study focuses on the effectiveness of school library services as a source of history learning at SMK Negeri 1 Siniu and on changes in student behavior after optimizing library services. This study aims to analyze the effectiveness of school library services in supporting history learning and to examine changes in student learning behavior resulting from the optimization of library services. The research method is qualitative, with a descriptive approach. Data collection was conducted through observation, interviews, and documentation, involving history teachers and students as research informants. The results of the study indicate that effectively managed library services can increase student motivation for learning, foster a comfortable learning environment, and encourage active student participation in history learning. In addition, the optimization of library services contributes to positive changes in student learning behavior, as reflected in increased use of the library as a space for daily tests, learning discussions, and the development of students' social skills and critical thinking.